Spectrophotometric analysis of magnetic white dwarf: II. Helium-rich compositions - François, Hardy von; Dufour, Patrick; Jordan, Stefan (Monthly notices of the Royal Astronomical Society, 2023)
We present an analysis of all single white dwarf stars known to exhibit spectroscopic signatures of neutral helium line splitting due to the presence of a strong magnetic field. Using state-of-the-art models taking into account the effects of magnetic fields on the synthetic spectra, we determine effective temperatures, surface gravities, and masses for the stars in our sample. ...